Changing trend in reading habits of teenagers in Delhi: An impact assessment of demographic and environmental variables. Issue 1 (2nd May 2014) - Walia, Paramjeet Kaur; Sinha, Nitu
Abstract : Purpose: – The purpose of this study was to attempt to answer some plausible questions like what do teenagers prefer to read at leisure, how do they read and why do they read? With the rapid changes in information technology, there is tremendous change in means of communication. Today, much more information is available from electronic and digital media as compared to traditional books. A paradigm shift in information delivery from just information to infotainment has also affected the preferences of the information seekers. Teenagers are a demographic group under transition and they are not untouched by these rapid changes in technology and their impact on their reading preferences. Design/methodology/approach: – For this purpose, a survey among 223 school-going (public/convent and government-/aided) teenagers aged between 12 and 18 years was done using a semi-structured questionnaire. Findings: – The findings revealed a decline in sports and outdoor recreational activities during leisure, and only 20.6 per cent teenagers preferred reading during leisure. However, self-perception as an avid reader was expressed by majority (53.8 per cent). Fictions were liked by > 75 per cent teenagers; however, non-fictions were also liked by majority (61.8 per cent). The reading preferences of the children were found to be affected by their age, their gender and the type of schools they attended. A significant inverse relationship of television watching and movie-going was observed with reading time. Research limitations/implications: – The biggest limitation was inability to directly interact with the students and inability to gather data from more schools. Practical implications: – By knowing the current reading trends, leisure time habits and exposure to different means of information technology, the choice of medium for knowledge dispersal could be done. The study would help in providing a basis for a strategic change in the ratio of conventional books and other information media in the library. Social implications: – By identifying the media exposure time and popularity, proper steps may be taken in order to enrich the particular media and to ensure that quality of information available on the media can be directed for social benefit in large. Originality/value: – The impact of demographic and environmental variables on reading habits of teenagers has not been evaluated in this part of the world, especially in view of the paradigm shift in information technology and the growing influence of electronic media and social networking. An understanding of this mutual relationship would help in modifying the reading behaviour of the teenagers.